2019
DOI: 10.3390/s19194288
|View full text |Cite
|
Sign up to set email alerts
|

Application-Based Production and Testing of a Core–Sheath Fiber Strain Sensor for Wearable Electronics: Feasibility Study of Using the Sensors in Measuring Tri-Axial Trunk Motion Angles

Abstract: Wearable electronics are recognized as a vital tool for gathering in situ kinematic information of human body movements. In this paper, we describe the production of a core–sheath fiber strain sensor from readily available materials in a one-step dip-coating process, and demonstrate the development of a smart sleeveless shirt for measuring the kinematic angles of the trunk relative to the pelvis in complicated three-dimensional movements. The sensor’s piezoresistive properties and characteristics were studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 83 publications
(131 reference statements)
1
36
0
Order By: Relevance
“…Tormene et al concluded that their prototype was able to monitor forward, but not lateral, bending and proposed the placement of additional sensors [28]. Rezaei et al proposed a wearable garment for monitoring three-dimensional movements of trunk [18]. In addition to the higher number of resistive sensors used in that prototype, the calibration was a tedious step involving implementing a machine-learning algorithm to train a model for detecting different postures [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tormene et al concluded that their prototype was able to monitor forward, but not lateral, bending and proposed the placement of additional sensors [28]. Rezaei et al proposed a wearable garment for monitoring three-dimensional movements of trunk [18]. In addition to the higher number of resistive sensors used in that prototype, the calibration was a tedious step involving implementing a machine-learning algorithm to train a model for detecting different postures [18].…”
Section: Discussionmentioning
confidence: 99%
“…Rezaei et al proposed a wearable garment for monitoring three-dimensional movements of trunk [18]. In addition to the higher number of resistive sensors used in that prototype, the calibration was a tedious step involving implementing a machine-learning algorithm to train a model for detecting different postures [18]. The prototype presented in this paper uses a single sensor to monitor forward bending and to distinguish it from lateral bending or twisting without requiring a lengthy calibration step.…”
Section: Discussionmentioning
confidence: 99%
“…f sensor is the sensor oscillation frequency in Hz, f REFx is the reference frequency in the chip, which was set to 40 MHz, L ( t ) is inductance in Henries, and C is the sum of sensor's capacitance and parasitic capacitance. The parasitic capacitance of the coil is negligible in comparison with the selected chip capacitance—which was 330 pF and chosen to match the inductance—which was constant …”
Section: Methodsmentioning
confidence: 99%
“…To achieve a sufficient signal with good sensitivity, inductive sensors can encompass a larger area, use multiple perimeter coils, and use higher magnetic permeable materials . Textile‐based inductive sensor technology is under‐represented compared with piezoresistive and capacitive sensors and is yet to be used for multiaxial kinematic motion tracking . Previously, wearable inductive‐based motion tracking sensors have been developed by enclosing an area with conductive thread or wire and have been used to track single‐axis motion including joints such as the elbow or knee, body posture, and skin deformation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation